Pelatihan Perwasitan Olahraga Tradisional Di Desa Karangsegar, Kecamatan Pebayuran - Nurmachmud, Septian; Alfredo, Alfredo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam 45 Bekasi, 2024)
The purpose of this study was to provide training and understanding of traditional sports refereeing in Karangsegar Village, Pebayuran District. The target of this study is residents of Karangsegar Village, especially sports teachers and adults over the age of 20 years, both men and women. Now we can see children carrying gadgets wherever they are, they are engrossed in their gadgets in hand while playing the games in it. I want to restore traditional games such as enggrang, obstacle, dagongan, engklek and so on that have been abandoned to become popular again. Even what was just a traditional game can now be developed into a contested sport. In addition, I also want to provide training on traditional sports refereeing so that people can not only play, but also be able to become referees or referees in traditional sports. To be able to realize this, I conducted qualitative research with observation, socialization, interview, and documentation methods in data collection. Then a research was carried out in the form of socialization and training for traditional sports refereeing at SDN Sumbersari 01 on March 4, 2023 with 25 participants who are sports teachers in Pebayuran District. The result of these activities is that PE teachers gain knowledge about traditional sports refereeing, PE teachers gain experience with hands-on practice on the field, and for a long period of time they can establish a traditional sports community in Pebayuran District to create quality athletes and referees.